2016
DOI: 10.14739/2310-1210.2016.1.63870
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix and left atrial remodeling in patients with ischemic chronic heart failure and renal dysfunction

Abstract: №1 (94) 2016 Х ронічна серцева недостатність (ХСН) є однією з основних медичних та епідеміологічних проблем. Ремоделювання серця -важливий чинник, що визначає клі-нічний результат ХСН, оскільки пов'язано з прогресуванням захворювання та несприятливим прогнозом. Незалежно від етіології, процес ремоделювання є загальним механізмом для прогресування ХСН. Ремоделювання відбувається у структурному компоненті міокарда -екстрацелюлярному матриксі (ЕЦМ), котрий постійно синтезується, деградує та є невід'ємною частиною… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Of these, 57 duplicate citations and 223 ineligible studies were excluded for the following reasons: That the study was an experimental or animal study, review article, or outcome of the study was not related to AF or galectin‐3. Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 57 duplicate citations and 223 ineligible studies were excluded for the following reasons: That the study was an experimental or animal study, review article, or outcome of the study was not related to AF or galectin‐3. Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%